Development and validation of UPLC-MS/MS method for icariin and its metabolites in mouse urine - Li, Na; Yuan, Mei; Che, Jinjing (Frontiers in Pharmacology, 2024)
An ultra-performance liquid chromatography-tandem mass spectrometry (UPLC-MS/MS) method was utilized to develop a technique for the simultaneous quantification of icariin and its primary metabolites in mouse urine. The levels of icariin, icariside Ⅰ, icariside Ⅱ, baohuoside Ⅱ, wushanicaritin, icaritin, and desmethylicaritin in mouse urine were analyzed subsequent to the oral administration of an icariin suspension. This study aimed to preliminarily investigate the excretion profile of icariin in mice. Using an aqueous solution containing 0.1% formic acid (A) and an acetonitrile solution containing 0.1% formic acid (B) as the mobile phases, icariin and its major metabolites demonstrated satisfactory linearity over the concentration range of 0.25-800 ng•mL-1. The precision and accuracy of intra-day and inter-day measurements were all found to be within 15%. 72 hours after the intragastric administration of icariin suspension to a mouse, the cumulative urinary excretion of icariin, icariside Ⅰ, icariside Ⅱ, baohuoside Ⅱ, wushanicaritin, icaritin, and desmethylicaritin was quantified as 13.48, 18.70, 2627.51, 2.04, 10.04, 3420.44, and 735.13 ng, respectively. The UPLC-MS/MS method developed in this research is characterized by its simplicity, sensitivity, and speed, making it well-suited for the concurrent quantification of icariin and its associated metabolites in urine. Additionally, it is appropriate for analyzing urine samples that may contain multiple drugs in future investigations.